2008
DOI: 10.1021/bi702238b
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability Changes of Human IgG1 Fc as a Consequence of Methionine Oxidation

Abstract: The Fc region has two highly conserved methionine residues, Met 33 (C(H)3 domain) and Met 209 (C(H)3 domain), which are important for the Fc's structure and biological function. To understand the effect of methionine oxidation on the structure and stability of the human IgG1 Fc expressed in Escherichia coli, we have characterized the fully oxidized Fc using biophysical (DSC, CD, and NMR) and bioanalytical (SEC and RP-HPLC-MS) methods. Methionine oxidation resulted in a detectable secondary and tertiary structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(180 citation statements)
references
References 45 publications
12
168
0
Order By: Relevance
“…D. Liu et al reported analysis by DSC of mutants of Human IgG1 Fc that lacked either methionine residue analysis of Human IgG1 Fc demonstrated that oxidation of either methionine resulted in structural changes to the C H 2 and C H 3 domains, the results described here add further weight to this conclusion. 17 It may Figure 7. Positive ion MALDI mass spectra of glycans from oxidised and unoxidised GSK-mAb samples released using the PNGase F digestion protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…D. Liu et al reported analysis by DSC of mutants of Human IgG1 Fc that lacked either methionine residue analysis of Human IgG1 Fc demonstrated that oxidation of either methionine resulted in structural changes to the C H 2 and C H 3 domains, the results described here add further weight to this conclusion. 17 It may Figure 7. Positive ion MALDI mass spectra of glycans from oxidised and unoxidised GSK-mAb samples released using the PNGase F digestion protocol.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Liu et al analysed oxidised recombinant human IgG1 Fc that had been expressed in E. coli using a variety of biophysical and biochemical techniques. 17 Analysis by CD and NMR of an isotopically labelled Fc fragment showed that methionine oxidation resulted in detectable secondary and tertiary structural changes in the interface between the C H 2 and C H 3 domains. Differential scanning calorimetry (DSC) was used to measure the melting temperature (T m ) of the C H 2 and C H 3 domains.…”
Section: Introductionmentioning
confidence: 99%
“…Such analysis will provide the ability to assess the structural impact of a range of parameters, including post-translational modifications such as methionine oxidation. 52 In the case study of the small protein therapeutic filgrastim, resonance assignments allowed a detailed mapping of the structural effects for different formulation conditions. 53 For mAb therapeutics, the isolated Fab and Fc are known to retain a similar HOS to that observed for these fragments in the intact NISTmAb.…”
Section: Discussionmentioning
confidence: 99%
“…This increase is predictive of decreased long-term stability, as oxidation can trigger further degradation events such as aggregation. 28,32 Thus, MS emerged as a critical stability-indicating assay for the evaluation of oxidative degradation pathways.…”
Section: Effect Of Ps80 On Otelixizumab Stability In Vials and Selectmentioning
confidence: 99%